Inflation Dynamics in Kazakstan. (IMF Working Papers; Working Paper, 1995)
In January 1992, Kazakstan initiated a reform program to move toward market-determined prices. The price liberalization process was characterized by large relative price shifts and an increase in the overall price level toward those observed in market economies. The paper shows how the piecemeal manner in which prices were liberalized resulted in strong relative price variability over a prolonged period of time, against a background of high inflation. Convergence toward international relative and absolute price levels has progressed but is not complete, with prices for energy and services in particular still below market economy level.